Varenicline for smoking cessation: A placebo-controlled, randomized study - Chen Wang (2018)
Background and objective: Varenicline tartrate, a novel, selective, nicotinic acetylcholine receptor partial agonist, has been developed specifically as a smoking cessation drug. This study evaluated the efficacy of a standard regimen of varenicline compared with placebo for smoking cessation in 333 subjects in China, Singapore and Thailand. Methods: This 24-week, randomized, double-blind, placebo-controlled trial of varenicline, 1 mg bd, consisted of a 12-week treatment period followed by a 12-week non-treatment follow-up period. The primary study end-point was the 4-week continuous abstinence rate defined as the proportion of subjects who reported total abstinence from smoking and other nicotine products from weeks 9-12. A key secondary end-point was the continuous abstinence rate from weeks 9-24, defined as the proportion of subjects who achieved the primary end-point as well as total abstinence from all tobacco products from weeks 13-24. Results: Both end-points were achieved by a significantly higher proportion of subjects in the varenicline group than in the placebo group. The 4-week continuous abstinence end-point was achieved by 50.3% and 31.6% in the varenicline and placebo groups, respectively (P = 0.0003), while continuous abstinence from weeks 9-24 was achieved by 38.2% and 25.0% of subjects, respectively (P = 0.0080). The treatment effect was generalizable by treatment centre and country. Varenicline was safe and appeared to be well tolerated by most subjects. Conclusion: Varenicline was significantly more efficacious for smoking cessation than placebo over a 12-week treatment period and a further 12-week non-treatment follow-up period in smokers from China, Singapore and Thailand. No significant side-effects were noted. © 2009 Asian Pacific Society of Respirology.